РОЛЬ ИНСТИТУТА БАНКРОТСТВА В ПОСТРОЕНИИ ЭФФЕКТИВНОЙ СОЦИАЛЬНО-ОРИЕНТИРОВАННОЙ ЭКОНОМИКИ (Journal of Economic Research & Business Administration, 2015)
It is marked in article, that the institute of bankruptcy should carry out function makroeconomiks of strategy of the state. The characteristics of foreign models regulation inconsistency are given. The ways of development the institute of bankruptcy are given at a presidential control system of the Kazakhstan economy.